2020
DOI: 10.1080/0312407x.2020.1771389
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Social Workers’ Understanding of Australian First Nations Perspectives in Statutory Child Protection

Abstract: Chronic staff shortages and high rates of turnover in child protection programs create opportunities for social work mobility across the world. Australian child protection departments actively recruit social workers from the United Kingdom and Ireland. This strategy may cause tension relating to the application of known western social work practice and theory and limited understanding of Australian First Nations worldviews. Australia continues to struggle with the ongoing impact of colonisation, First Nations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…These studies, which range from small qualitative interviews with social work practitioners, to larger observational work, lend credence to the calls for decolonisation of social work curriculum (Gray et al, 2016). The article by Modderman et al (2021) explored the understandings that transnational social workers have about First Nations child protection practices when they come from the United Kingdom and Ireland to Australia, and the critical importance of cultural humility and counter-colonial thinking. Reflections by the social workers in this study elucidate the shame felt in being "white, female, English" and asked to remove a First Nations child, and the understanding of oppression and power shown in this statement: "We're talking about an extremely oppressed community, who face trauma after trauma after trauma from White people.…”
Section: Claiming and Expanding Social Work Knowledge In The International Spacementioning
confidence: 99%
See 1 more Smart Citation
“…These studies, which range from small qualitative interviews with social work practitioners, to larger observational work, lend credence to the calls for decolonisation of social work curriculum (Gray et al, 2016). The article by Modderman et al (2021) explored the understandings that transnational social workers have about First Nations child protection practices when they come from the United Kingdom and Ireland to Australia, and the critical importance of cultural humility and counter-colonial thinking. Reflections by the social workers in this study elucidate the shame felt in being "white, female, English" and asked to remove a First Nations child, and the understanding of oppression and power shown in this statement: "We're talking about an extremely oppressed community, who face trauma after trauma after trauma from White people.…”
Section: Claiming and Expanding Social Work Knowledge In The International Spacementioning
confidence: 99%
“…The articles in this Issue are extremely diverse in their topics and methodologies, yet all share a common theme of deep exploration into corners of social work that contribute much to knowledge. The international flavour to this Issue is evident in the publications from Australia (Gatwiri et al, 2021;Modderman et al, 2021), New Zealand (Fox, 2021), Ghana (Adonteng-Kissi, 2021), Israel (Alhuzail & Segev, 2021), Taiwan (Lee, 2021), China (Lei et al, 2021), and Hong Kong (Leung, 2021). The research reported through these selected publications include very largescale quantitative studies of social work student perspectives on the concept of "person-inenvironment" in China (see Lei et al, 2021), to social work student attitudes towards Indigenous peoples in Taiwan (see Lee, 2021).…”
Section: Claiming and Expanding Social Work Knowledge In The International Spacementioning
confidence: 99%
“…The koru model: The stages of biculturation for foreign-trained social workers in Aotearoa New Zealand Introduction Like many professions, social work has experienced the impact of globalisation. This is demonstrated by social work being a profession very much "on the move", with various authors exploring the impact of an increasing transnational social work workforce (Bartley et al, 2011;Bartley & Beddoe, 2018;Hanna & Lyons, 2017;Modderman et al, 2020;Pullen-Sansfaçon et al, 2012). Many studies have explored the process of settlement or acculturation for migrants into new countries (Zapf, 1991).…”
Section: Qualitative Researchmentioning
confidence: 99%
“…"While warmly welcomed and occasionally given a superficial introduction to Māori culture, many found there was no induction process that helped participants comprehend cultural, social and political aspects of New Zealand social work" (p. 2018). Modderman et al (2020) reported on a study of English and Irish social workers who emigrated to practise in child welfare in Australia. The article explored the knowledge regarding Australian First…”
Section: Social Workmentioning
confidence: 99%
“…5,9,10 Such limitations are particularly impactful on First Nations children who experience higher rates of removal from their homes and cultures than non-Indigenous children 1 ; reflecting the ongoing impact of colonisation and systemic denial of human rights for this group of people. 11 At present, most Aboriginal community-controlled health services do not have sufficient resources to provide the health assessments and services needed for First Nations children in OOHC. 12 Several national and state-based policies are tackling the issue of health care for vulnerable children.…”
Section: Introductionmentioning
confidence: 99%